Teaching Early-Level Foreign Languages to Pupils with Impaired Pronunciation Abilities - Janíková, Věra (Revija za elementarno izobraževanje, 2009)
Today, teaching and learning early-level foreign languages has become a common issue often discussed by specialists. This article deals with the problems of foreign language pronunciation for primary level pupils with impaired communication abilities. The article includes findings from special education and psychology reports along with a definition of the term impaired communication ability and the phonetic-phonological impact it has on learning a foreign language. The conclusion presents some chosen methods for teaching drama and theatre projects that deal with proper pronunciation training and the results of related research investigations.